INFLUENCE OF RELIGIOUS IDENTITY ON CONSUMER BEHAVIOUR: INSIGHTS FROM HINDU SUB-SECTS IN AHMEDABAD (GUJARAT) - Nayee, Paresha J.; Rathod, Harishchandra Singh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Analyzing consumer behaviour requires careful understanding of religious and cultural consequences. For marketers, targeting to succeed in different market, identifying and adopting these factors are very important. In India, Each state have its own well-defined culture, lifestyle and language. Specifically, Gujarat stands out as progressive state, performing an important role in India’s economic improvement and cultural identification. This study examines the impact of religion on selected sub-sect of Hindu consumer’s buying behaviour in Ahmedabad, Gujarat. Data was collected from 203 respondents across Ahmedabad, Gujarat by using a non-probability convenience sampling method. Four sub-sect of Hindu religion like BAPS (Bochasanwasi Akshar Purushottam Swaminarayan Sanstha), Swaminarayan Mandir Vasna Sanstha (SMVS), ISKCON (International Society for Krishna Consciousness) and Brahmakumaris was taken to analyze the impact. Cluster analysis and ANOVA test was performed to check the impact of religion on all four clusters